Analisis Hukum Sebagai Agen Pengendali Sosial Dalam Masyarakat Ditinjau Dari Sosiologi Hukum - Sapanah, Mawar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article aims to fulfill the final exam assignment of the semester, the fourth semester of Law and society taught by lecturer Kayus Kayowuan Lewoleba S.H,.M.H. as well as additional knowledge for us about the importance of law, from the perspective of legal sociology, as a means of social control in society. the method used by the author is Normative legal research, often known as normative juridical research, is the methodology used. Normative juridical research method is a type of legal research conducted solely using secondary data or library materials. The purpose of this research is to collect relevant sources in the form of theories, conceptions, legal guidelines, and legal principles. The author takes data collection through library research, namely research sources in the form of reading journals and books that discuss with Law can control human behavior, which is why law is called a social control agent. This action can be considered a positive action because it deviates from the law. Therefore, the law has the authority to punish or penalize individuals who violate the law (offense). This implies that in order for society to achieve peace together, the law must play a role in guiding members of society to act and behave in accordance with the law.